DNA Binding Studies on the Interaction of Myricetin-Bi(III) Complex with Double Stranded DNA by UV-VIS Spectrophotometry and Voltammetry - Hajian, R.; Iravani, N.; Ghanbari, F.; Shams, N. (Asian Journal of Chemistry, 2012)
The interaction of bismuth(III) complex of 3,5,7-trihydroxy-2-(3,4,5-trihydroxyphenyl)-4- chromenone known as myricetin with calf thymus double stranded ds-DNA has been investigated using UV-visible spectrophotometry and electrochemical techniques. The observation of an isosbestic point at 312 nm follow by a hypochromicity at 326 nm showed the formation a new complex between bismuth ion and myricetin. The calibration curves for ds-DNA in the absence and presence of Bi(III)-myricetin complex differ significantly in the slopes due to the interaction between two species. The electrochemical behaviour of the new complex bound to ds-DNA has been compared with myricetin alone as a flavonoid. As a result of the interaction with ds-DNA, the reduction peak current related to Bi(III)-myricetin decreased by increasing concentration of ds-DNA. The diffusion coefficients of the complex in the absence (Df) and presence (Db) of ds-DNA were calculated as 5.37 × 10-7 cm2 s-1 and 4.55 × 10-7 cm2 s-1 respectively. The binding constant (K = 9.0 × 104 L mol-1) and binding site size (s = 0.80) of the complex-myricetin interacting with ds-DNA were obtained simultaneously by non-linear fit analysis. The DNA binding constant determined reveal that the Bi(III)-myricetin complex interact with ds-DNA electrostatically due to the coulombic interactions.